Developmental and hormonal regulation of the arabidopsis CER2 gene that codes for a nuclear-localized protein required for the normal accumulation of cuticular waxes. - Xia, Y (1997)
The previously cloned CER2 gene is required for the normal accumulation of cuticular waxes and encodes a novel protein. Earlier reports suggested that the CER2 protein is either a membrane-bound component of the fatty acid elongase complex or a regulatory protein. Cell fractionation and immunoblot analyses using polyclonal antibodies raised against a chemically synthesized peptide with a sequence based on the predicted CER2 protein sequence have demonstrated that the 47-kD CER2 protein is soluble and nuclear localized. These results are consistent with CER2 being a regulatory protein. Detailed studies of plants harboring a CER2 promoter/GUS transgene (CER2-GUS), in combination with immunoblot analyses, revealed that CER2 is expressed and the CER2 protein accumulates in a variety of organs and cell types. Expression is highest early in the development of these organs and is epidermis specific in most tissues. In agreement with the activity of the CER2 promoter in hypocotyls, cuticular wax accumulates on this organ in a CER2-dependent fashion. In leaves CER2 expression is confined to the guard cells, trichomes, and petioles. However, application of the cytokinin 6-benzylaminopurine induces ectopic expression of CER2-GUS in all cell types of leaves that emerge following treatment.